CONTRADICCIÓN ENTRE EL ART. 49 Y EL ART. 65 DE LA LEY DE MINERIA RESPECTO AL DERECHO DE LIBRE COMERCIALIZACIÓN - ARMIJOS CH., DORIS PATRICIA (2016)
Mining is the economic, commercial and industrial action based on the exploration and extraction of mineral wealth found in the soil and subsoil, for which purpose there are mines and mineral exploitation in its various forms. In mining we have the large-scale mining and small-scale and artisanal mining. In turn, the mining sector has become a source of employment, direct labor, indirect labor, technical work, which promotes one way or another professional development of all human personnel immersed in this branch. Today mining activity has to meet standards of environmental character, the same as trying to ensure care for the environment at all stages of the activity until the end of it. I totally agree that mining is controlled, however, and there is excessive control by the State addressed, when it refers to the free marketing of minerals in small-scale and artisanal mining. Focusing on the free marketing, as provided in Article 49 of the Mining Act. "Holders of mining concessions may freely market their products inside or outside the country. However, in the case of gold from small-scale and artisanal mining, the Central Bank of Ecuador made marketing directly or through public and private economic agents previously authorized by the Bank. "So, we can give account and say that large-scale mining can do so freely inside or outside the country, in contrast to the small miners or artisanal miners only what made through the Central Bank of Ecuador, making their marketing directly or through traders Public and Private previously authorized by the Bank. That is why I consider it necessary to review the causes and consequences that cause the vulnerability of law in the small-scale and artisanal mining not be allowed to freely sell the gold, and in turn to contribute through this research to give a solution practicable to the problem that has been raised in the research project. Thus, in regard to the provisions of the Mining Law is causing economic harm to restrict the marketing of gold in small-scale miners and in turn is contrary to our constitution as enshrining the principle of equality and non- discrimination of all citizens who are part Constitutional State of Rights and Justice.